Rationale and design of the AMULET study: A new Model of telemedical care in patients with heart failure - Paweł Krzesiński; Janusz Siebert; Ewa Anita Jankowska; Waldemar Banasiak; Katarzyna Piotrowicz; Adam Stańczyk; Agata Galas; Andrzej Walczak; Piotr Murawski; Paweł Chrom; Piotr Gutknecht; Paweł Siwołowski; et al. (ESC Heart Failure, 2021)
Abstract Aims Heart failure (HF) is characterized by high mortality and hospital readmission rates. Limited access to cardiologists restricts the application of guideline‐directed, patient‐tailored medical therapy. Some telemedicine solutions and novel non‐invasive diagnostic tools may facilitate real‐time detection of early HF decompensation symptoms, prompt initiation of appropriate treatment, and optimal management of medical resources. We describe the rationale and design of the AMULET trial, which investigates the effect of comprehensive outpatient intervention, based on individualized haemodynamic assessment and teleconsultations, on cardiovascular mortality and unplanned hospitalizations in HF patients. Methods and results The AMULET trial is a multicentre, prospective, randomized, open‐label, and controlled parallel group trial (ClinicalTrials.gov Identifier: NCT03476590). Six hundred and five eligible patients with HF (left ventricular ejection fraction ≤49%, at least one hospitalization due to acute HF decompensation within 6 months prior to enrolment) were randomly assigned in a 1:1 ratio to either an intervention group or a standard care group. The planned follow‐up is 12 months. The AMULET interventions are performed in ambulatory care points operated by nurses, with the remote support of cardiologists. The comprehensive clinical evaluation comprises measurements of heart rate, blood pressure, body mass, thoracic fluid content, and total body water. A recommendation support module based on these objective parameters is implemented in remote therapeutic decision‐making. The primary complex endpoints are cardiovascular mortality and unplanned HF hospitalization. Conclusions The AMULET trial will provide a prospective assessment of the effect of comprehensive ambulatory intervention, based on telemedicine and haemodynamically guided therapy, on mortality and readmissions in HF patients.